Inflammation: a common contributor to cancer, aging, and cardiovascular diseases—expanding the concept of cardio-oncology. Issue 5 (4th March 2019) - Libby, Peter; Kobold, Sebastian
Abstract: Inflammation participates in the pathogenesis of both cancer and cardiovascular disease. This review examines the mechanistic commonalities between these two scourges of humanity through the lens of inflammation biology. Inflammatory pathways contribute to the initiation, the progression, and the complication of both malignant tumours and atherosclerotic plaques. Modulation of inflammatory pathways have proven transformative in the treatment of cancers and have crossed the threshold of clinical reality as treatments to reduce the risk of cardiovascular events. The finding that clonal haematopoiesis drives both leukaemia and cardiovascular events provides yet another link between these two seemingly disparate diseases. The nascent specialty of cardio-oncology has initially focused on the cardiovascular complications of cancer therapies. The recognition of a more profound pathophysiologic connection between cancer and cardiovascular diseases should expand the concept of cardio-oncology. Embracing the mechanistic connection and transcending traditional barriers between disciplines offers immense opportunities for speeding innovative research that can address the growing burden of both cancer and cardiovascular disease.